Integrated bioinformatic and phenotypic analysis of RpoN-dependent traits in the plant growth-promoting bacterium Pseudomonas fluorescens SBW25. - Jones, J; Studholme, D; Knight, C; Preston, G (2007)
The alternative sigma factor RpoN is a key regulator in the acclimation of Pseudomonas to complex natural environments. In this study we show that RpoN is required for efficient colonization of sugar beet seedlings by the plant growth-promoting bacterium Pseudomonas fluorescens SBW25, and use phenotypic and bioinformatic approaches to profile the RpoN-dependent traits and genes of P. fluorescens SBW25. RpoN is required for flagellar biosynthesis and for assimilation of a wide variety of nutrient sources including inorganic nitrogen, amino acids, sugar alcohols and dicarboxylic acids. Chemosensitivity assays indicate that RpoN-regulated genes contribute to acid tolerance and resistance to some antibiotics, including tetracyclines and aminoglycosides. Gain of function changes associated with loss of RpoN included increased tolerance to hydroxyurea and Guanazole. Bioinformatic predictions of RpoN-regulated genes show a close correspondence with phenotypic analyses of RpoN-regulated traits and suggest novel functions for RpoN in P. fluorescens, including regulation of poly(A) polymerase. The reduced plant colonization ability observed for an rpoN mutant of P. fluorescens is therefore likely to be due to defects in multiple traits including nutrient assimilation, protein secretion and stress tolerance.